THE RESPONSE OF TUNNEL LINING ON THERMAL LOADING - Markéta Levorová; Radek Vašíček (Rudarsko-geološko-naftni Zbornik, 2012)
The long-term functionality, i.e. stability of the lining of disposal tunnels is a precondition for the safe removal and reprocessing of spent nuclear waste from deep underground repositories in the near or more distant future. The reason for removing containers with radioactive waste from such repositories lies in the potential development of presently unavailable “perfect” technology for its reprocessing. The stability problems of the tunnel lining exposed to the long-term thermal load generated by the waste in the disposal container was the subject of one task of the European TIMODAZ project (Thermal Impact on the Damaged Zone around a Radioactive Waste Disposal in Clay Host Rocks). Research was carried out by means of physical modeling. Although the project was terminated in September 2010, recorded data is being further analyzed. This paper describes the design, construction and results of an in-situ model which has been built at the Underground Research Centre Josef in the Czech Republic.